THE AGRICULTURAL SECTOR IN THE HYDROPONICS SECTOR IN IMPROVING THE HOUSEHOLD ECONOMY IN SIANTAN TENGAH - Dina Khairunnisa (Journal of Islamic Economy and Business (JIsEB), 2023)
Introduction/ Purpose: This study aims how people who grow some vegetables using hydroponics become easier and more practical in improving the household economy. Hydroponics is the choice of the agricultural sector for people who do not have large areas to grow crops. The purpose of holding a hydroponic program is to make members of farmer groups independent in the economy. Research Methods: This study uses primary data qualitative research, the researcher observes the phenomena around it without any numerical measurements by analyzing in-depth case studies in the Central Siantan village. Results: The results of this research are hydroponics can improve household economy because it can become independent in the agricultural sector in food for daily consumption. The household economy is no longer dependent on high market prices, but we can even create household income.